2014
DOI: 10.1097/cad.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of lipophilic statins depends on their combined actions on HIF-1α expression and redox status in B16.F10 melanoma cells

Abstract: Statins, as inhibitors of de-novo synthesis of cholesterol, exert cytotoxic actions on tumor cells. Despite the increasing data on the antitumoral activities of statins, their complete mechanisms of action still remain obscure. Therefore, the present study aims to investigate the mechanisms of lipophilic statin-induced cytotoxicity on B16.F10 murine melanoma cells in vitro. In-vitro effects of two lipophilic statins, simvastatin and lovastatin, and a hydrophilic statin, pravastatin, were investigated with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 51 publications
2
31
0
1
Order By: Relevance
“…The present study provides a follow-up of our earlier observations that inhibition of the constitutive expression of HIF-1α in B16.F10 murine melanoma cells is one of the main reasons behind the cytotoxicity caused by lipophilic statins on these cancer cells (1). Therefore, the present study evaluated whether this finding could be expanded under hypoxic conditions, when the constitutive production of HIF-1α in B16.F10 melanoma cells is accompanied by its induced expression as a result of CoCl 2 -mediated transcription factor stabilization and activation (28).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The present study provides a follow-up of our earlier observations that inhibition of the constitutive expression of HIF-1α in B16.F10 murine melanoma cells is one of the main reasons behind the cytotoxicity caused by lipophilic statins on these cancer cells (1). Therefore, the present study evaluated whether this finding could be expanded under hypoxic conditions, when the constitutive production of HIF-1α in B16.F10 melanoma cells is accompanied by its induced expression as a result of CoCl 2 -mediated transcription factor stabilization and activation (28).…”
Section: Discussionmentioning
confidence: 74%
“…3B). Our previous results have shown that SIM inhibited strongly the constitutive expression of HIF-1α in B16.F10 murine melanoma cells at a concentration 10-fold higher than that used in the present study (1). Regarding the production of NF-κB, SIM treatment did not affect the expression levels of this transcription factor under normoxic or hypoxic conditions (Fig.…”
Section: Effects Of Sim On the Expression Levels Of Hif-1α And Nf-κbmentioning
confidence: 76%
See 2 more Smart Citations
“…Dessa forma, o sal de tetrazólio poderá ser utilizado como um indicador bioquímico da maturidade fisiológica da semente. É essencial destacar que em outras áreas da ciência, o sal de tetrazólio é utilizado para avaliar a viabilidade de células vegetais e animais e para acompanhar o desenvolvimento das células, em várias pesquisas das áreas de medicina e de microbiologia (ALUPEI et al, 2014;JUNILLON;FLANDROIS, 2014;WANG et al, 2014 Lakon (1940Lakon ( , 1942; no entanto, seu trabalho só foi conhecido na América após a II Guerra Mundial, quando foram entrevistados cientistas alemães (DELOUCHE et al, 1976 Além dessas duas enzimas, existem inúmeras proteínas que atuam em diversos ciclos para permitir a funcionalidade e o pleno desenvolvimento dos tecidos meristemáticos e os tecidos de reserva. Por isso que é necessário conhecer o exato momento em que a semente chega a sua plena maturidade findando o ciclo de formação e entrando no estágio de quiescência e se preparando para germinar no momento oportuno.…”
Section: Revisão Bibliográficaunclassified